Pelatihan Penggunaan Media Sosial Pada UMKM Nila Banjar Indah - Mailita; Idiannor Mahyudin; Emmy Sri Mahreda; Emmy Lilimantik; Tri Dekayanti; Ulfah Riani, Maria; Aswin (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
The Nila Banjar Indah MSME has so far relied solely on conventional marketing, such as bazaars run by relevant agencies, to market its products, even though several of its competitors have embraced digital marketing. To compete, this MSME needs to develop digital marketing efforts, particularly on social media. Digital training was conducted as an effort to increase the marketing capacity of MSMEs in Nila Banjar Indah through the utilization of digital technology. During the activity, participants were given a basic understanding of the importance of digital marketing in the modern economic era, as well as practical training on the use of social media, marketplaces, and other digital tools to market processed tilapia products effectively. The extension activities consisted of 4 sessions, namely a pre-test, provision of materials and training, discussions, and a post-test. Before the extension activities were carried out, a pre-test was conducted with a pre-test calculation result of 31% and after the activities were carried out, a post-test was carried out with a calculation result of 69% which indicated that initially some participants did not know much about digital marketing. However, after the extension activities were carried out, several digital marketing tools were created in its implementation through FB, Instagram, and Tik Tok to expand the market. It is hoped that the creation of social media as a digital marketing tool will gradually increase the profits of the Nila Banjar Indah MSME by expanding its market share, which has previously relied solely on existing customers. This digital marketing strategy will help it compete with similar MSMEs and larger companies operating in the same area as the Nila Banjar Indah MSME.